COHERENCE BETWEEN URBAN FARMING PROGRAMME AND ADIWIYATA SCHOOL PROGRAMME: INTEGRATING FOOD SECURITY POLICY IN SUSTAINABLE HUMAN RESOURCE DEVELOPMENT - Alifa Hasnggawurihansi; Jusuf Irianto; Bintoro Wardiyanto (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
The link between food security and sustainable resource development is a strategic component of the national development agenda. Urban agriculture has been embraced as an innovative solution to the challenge of limited agricultural land in urban areas, serving as a significant step towards achieving sustainable resource development through contextualized learning. The Adiwiyata School Programme, a policy of the Ministry of Environment, can be seen as part of the Sustainable Human Resource Development structure at the primary and secondary education levels, where environmental values and awareness are integrated. These include character and social responsibility, independence and life skills, creativity and innovation, and recognition of the importance of sustainable food security. However, the implementation of these two policies at the local level reveals a variety of approaches influenced by local government commitment, institutional capacity, and cross-sector coordination. This research aims to analyze the coherence of the urban agriculture policy with the Adiwiyata school program and identify challenges faced by local governments in integrating the two policies. A qualitative approach, utilizing the literature study method, was chosen as the data collection technique, which was then analyzed using the Policy Coherence Framework. Based on this platform, we will examine the level of alignment between different policies to enable synergy in their implementation. The research findings are expected to provide insights and support for the achievement of policy objectives, especially through coherent synergies between policies, as well as offer recommendations for policy formulation at the local level to enhance food security and sustainable human capital development